Bioinformatics analysis identifies ZBTB16 as a potential immune biomarker for lung cancer and pan-cancer - Shi, Danfei; Cai, Yunxiang; Zhu, Di; Li, Xinmin; Li, Yong (Frontiers in Genetics, 2025)
ObjectiveLung cancer (LC) is a deadly cancer and a challenging public health problem worldwide. The aim of this study is to use bioinformatics to analyze the potential of ZBTB16 as an immune biomarker in lung cancer and various other cancers.MethodsOverlapping differentially expressed genes (DEGs) in LC were selected from GSE3268, GSE 1987, GSE31547 and GSE18842 gene expression data sets. We conducted a comprehensive bioinformatics analysis of these differentially expressed genes, aiming to explore their enrichment functions and pathways, relative expression levels, interaction networks, and weighted gene co expression network (WGCNA) module analysis. Then, the potential role of ZBTB16 in the occurrence and progression of lung cancer was verified, and immune invasion analysis, pan-cancer analysis and mRNA-miRNA link analysis were performed.ResultsThere were 16 genes with increased expression and 100 genes with decreased expression. Among them, KEGG analysis showed that these DEGs were significantly involved in complement and coagulation cascades, as well as related pathways such as proximal tubular bicarbonate recovery. Previous studies have shown that ZBTB16 plays an important role in various systemic tumors, but its function in lung cancer has not been revealed. WGCNA analysis shows that ZBTB16 is significant in lung cancer. Therefore, we will focus our attention on ZBTB16. Then, TCGA database, Human Protein Atlas database, and whole blood qPCR testing were used to verify the differential expression of ZBTB16 in lung cancer, and immune invasion analysis of ZBTB16 in lung cancer, pan cancer analysis of ZBTB16, and mRNA miRNA linkage analysis of ZBTB16 were performed.ConclusionThree validation methods and pan cancer analysis all showed that the expression of ZBTB16 was reduced in lung cancer and various cancers, which may be a key gene for the occurrence and development of lung cancer and various cancers.